Zampanolide, a Microtubule-Stabilizing Agent, Is Active in Resistant Cancer Cells and Inhibits Cell Migration - Field, Jessica J. (Int J Mol Sci, 2017)
Zampanolide, first discovered in a sponge extract in 1996 and later identified as a microtubule-stabilizing agent in 2009, is a covalent binding secondary metabolite with potent, low nanomolar activity in mammalian cells. Zampanolide was not susceptible to single amino acid mutations at the taxoid site of β-tubulin in human ovarian cancer 1A9 cells, despite evidence that it selectively binds to the taxoid site. As expected, it did not synergize with other taxoid site microtubule-stabilizing agents (paclitaxel, ixabepilone, discodermolide), but surprisingly also did not synergize in 1A9 cells with laulimalide/peloruside binding site agents either. Efforts to generate a zampanolide-resistant cell line were unsuccessful. Using a standard wound scratch assay in cell culture, it was an effective inhibitor of migration of human umbilical vein endothelial cells (HUVEC) and fibroblast cells (D551). These properties of covalent binding, the ability to inhibit cell growth in paclitaxel and epothilone resistant cells, and the ability to inhibit cell migration suggest that it would be of interest to investigate zampanolide in preclinical animal models to determine if it is effective in vivo at preventing tumor growth and metastasis.